Peripapillary and macular choroidal area in patients with normal-tension glaucoma - Kojima, Hirokazu (PLoS One, 2018)
PURPOSE: To evaluate normal and normal-tension glaucoma (NTG) eyes for differences in peripapillary and macular choroidal area measurements. METHODS: This cross-sectional comparative study enrolled 52 normal subjects and 35 NTG patients. Peripapillary and macular choroidal images were recorded by enhanced depth imaging optical coherence tomography (EDI-OCT), with conversion of the luminal and interstitial areas to binary images performed using the Niblack method. RESULTS: While there was a significant difference between normal subjects and NTG patients for the peripapillary choroidal area (1,853,672 ± 626,501 μm(2) vs. 1,606,448 ± 418,214 μm(2), P = 0.047), there were no significant differences between the normal subjects and NTG patients observed for the macular choroidal area (345,365 ± 119,248 μm(2) vs. 316,442 ± 85,732 μm(2), P = 0.23). In the NTG patients, multivariate regression analysis demonstrated a correlation between the macular choroidal area and the axial length (β = -0.345, P = 0.04). Furthermore, there was also a significant correlation between the peripapillary choroidal area and the age of the NTG patients (β = -0.469, P = 0.004). In addition, there was no relationship between the glaucoma severity and the peripapillary and macular choroidal areas in the NTG patients. CONCLUSIONS: There was no correlation between the peripapillary choroidal area and glaucoma severity in NTG patients, even though the area was smaller in these patients.